Model Frekuensi Kritis Lapisan Ionosfer Pada Kawasan Timur Indonesia - Habirun Habirun; Anwar Santoso (Indonesian Journal of Physics, 2002)
The ionospheric layer have been influenced by the ionosphere daily variation especially variation of the result of solar effects and variation of which have been caused by moon pulling energy so that the characteristic of the foF2 critical frequency ionospheric layer characteristics a certain pattern. Besides that disturbance, the ionospheric layer can also be influenced by pertubation of the earth’s magnetic field variation and local time. Therefore on this description will be discussed of the foF2 critical frequency ionospheric layer model on Indonesia east region with using to polinom tree order model. The model calculation is based on geographic latitude that correlated to earth’s magnetic field variation and local time.